Azathioprine induced cholestatic hepatitis - Moses, Viju (Medknow Publications & Media Pvt Ltd, 2011)
We report a case of cholestatic hepatitis developed one week after exposure to azathioprine. The subsequent prolonged cholestatic phase was followed by full clinical remission. Current knowledge on pathogenesis and epidemiology and the diagnostic challenges presented by this rare complication are discussed, followed by recommendations for monitoring and management.